2007
DOI: 10.1089/bfm.2006.0031
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding or Breastmilk to Alleviate Procedural Pain in Neonates: A Systematic Review

Abstract: If available, breastfeeding or breastmilk should be used to alleviate pain in neonates undergoing painful procedure compared to placebo, positioning, or no intervention. Administration of glucose/sucrose had a similar effectiveness as breastfeeding for reducing pain. The effectiveness of breastmilk for repeated painful procedures is not established, and further research is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 35 publications
0
12
0
1
Order By: Relevance
“…9 Breastfeeding combines several analgesic effects (a comforting person [mother], skinto-skin contact, diversion of attention, and the sweetness of lactose) as effective for procedural pain. [23][24][25] Unfortunately, if the mother is no longer breastfeeding or if she would rather not breastfeed while the baby receives immunizations, than alternative analgesic techniques are necessary.…”
Section: Resultsmentioning
confidence: 99%
“…9 Breastfeeding combines several analgesic effects (a comforting person [mother], skinto-skin contact, diversion of attention, and the sweetness of lactose) as effective for procedural pain. [23][24][25] Unfortunately, if the mother is no longer breastfeeding or if she would rather not breastfeed while the baby receives immunizations, than alternative analgesic techniques are necessary.…”
Section: Resultsmentioning
confidence: 99%
“…16 Breastfeeding is considered a combined analgesic intervention because several aspects of breastfeeding (e.g., holding the child, skin-to-skin contact, the sweet-tasting milk and the act of sucking) may individually attenuate pain responses.…”
Section: Breastfeedingmentioning
confidence: 99%
“…Offering breast milk or formula via a bottle should not be considered a substitute for breastfeeding as a method of reducing pain. 16 There are no reports of adverse events, such as gagging or spitting up. Compared with the frequency of breastfeeding, vaccine injections are uncommon, and it is unlikely that an infant will associate breastfeeding with painful procedures.…”
Section: Clinical Considerationsmentioning
confidence: 99%
“…34 On the other hand, a systematic literature review that compared the reaction of newborns who were breastfed or who received expressed breast milk during painful procedures with controls (placebo, pacifier, sugary solutions or position) concluded that the breastfed group showed a lower increase in heart rate and cried less than the group who used the pacifier or was wrapped in swaddling cloths. 35 This review also showed that the effect of the administration of sugary solutions is similar to the effect caused by breastfeeding. Nevertheless, further studies are necessary so that the effect of expressed breast milk can be understood in such situations.…”
Section: Psychologymentioning
confidence: 89%